2005
DOI: 10.1073/pnas.0500722102
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a bacterial BLUF photoreceptor: Insights into blue light-mediated signal transduction

Abstract: Light is an essential environmental factor, and many species have evolved the capability to respond to it. Blue light is perceived through three flavin-containing photoreceptor families: cryptochromes, light-oxygen-voltage, and BLUF (sensor of blue light using flavin adenine dinucleotide, FAD) domain proteins. BLUF domains are present in various proteins from Bacteria and lower Eukarya. They are fully modular and can relay signals to structurally and functionally diverse output units, most of which are implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
279
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(292 citation statements)
references
References 35 publications
12
279
1
Order By: Relevance
“…4). Finally, the short BLUF protein, BlrB from R. sphaeroides, adapts a very similar [AB] dimer form in its crystal structure (Protein Data Bank ID code 2BYC) (23). Collectively, these results suggest that PixD exists in solution as a stable [AB] dimer that oligomerizes in the dark with the help of PixE to form a stacked set of pentameric rings (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…4). Finally, the short BLUF protein, BlrB from R. sphaeroides, adapts a very similar [AB] dimer form in its crystal structure (Protein Data Bank ID code 2BYC) (23). Collectively, these results suggest that PixD exists in solution as a stable [AB] dimer that oligomerizes in the dark with the help of PixE to form a stacked set of pentameric rings (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Early studies suggested that an increased -stacking between Tyr and FAD, or deprotonation of FAD, would induce signaling-state formation (15,16). Jung et al (13) proposed that in the BlrB BLUF domain, proton transfer (PT) takes place from an arginine (Arg) residue to the O2 atom of the isoalloxazine ring upon blue-light absorption, triggered by the increased basicity of O2 upon promotion of FAD to the singlet excited state. Masuda et al (17) interpreted their results from Fourier transform infrared (FTIR) spectroscopy by a hydrogen-bond rearrangement around the FAD chromophore upon signaling-state formation.…”
mentioning
confidence: 99%
“…Recently, crystal and solution structures of several BLUF domains were obtained (11)(12)(13)(14). The BLUF domain shows a ferredoxin-like fold consisting of a five-stranded ␤-sheet with two ␣-helices packed on one side of the sheet, with the noncovalently bound isoalloxazine ring of flavin adenine dinucleotide (FAD) positioned between the two ␣-helices.…”
mentioning
confidence: 99%
“…Especially members of the BLUF 1 (blue light photoreceptors using FAD) family (1)(2)(3) show an especially intriguing light-induced proton network rearrangement resulting in a 10-15 nm red-shifted spectrum of the signaling state. The BLUF domain shows a ferredoxin-like fold consisting of a five-stranded β-sheet with two R-helices packed on one side of the sheet, with the isoalloxazine ring of flavin adenine dinucleotide (FAD) positioned between the two R-helices (4)(5)(6)(7)(8)(9)(10)(11)(12). FAD is noncovalently bound to the protein through a number of hydrogen bonds and hydrophobic interactions.…”
mentioning
confidence: 99%
“…Another aspect in the study of BLUF photoreceptors is their rather large variety in their transient behavior. Despite their high sequence homology the signaling state lifetime of BLUF domains varies from Slr1694, BlrB (5), and Thermosynechococcus TePixD (34) with around 10 s to AppA (35) and YcgF (36) with 50-100-fold slower decay times.…”
mentioning
confidence: 99%